VACTERL association with polycystic kidney disease in a newborn: a case report - Barboza, Joshuan J. (2021)
Malformations are important causes of infant mortality, chronic disease and disability in many countries, causing 3.2 million disabilities per year. The VATERL association includes vertebral defects, anal atresia, tracheoesophageal fistula and renal dysplasia, as well as limb abnormalities. This case report aims to provide the general characteristics of the VACTERL association and discuss other cases found in the medical literature. This is the case of a female newborn delivered at 35 weeks of pregnancy with severe respiratory distress, who was admitted to the neonatal ICU due to hemodynamic decompensation. She had a history of bilateral polycystic kidney disease found by ultrasound at 25 weeks of pregnancy. A physical examination showed vaginal agenesis and imperforate anus. Atelectasis, cardiomegaly and dextroposition of the cardiac silhouette were observed in a radiography. The patient was diagnosed with VACTERL association and imperforate anus. She died 2 days after a respiratory arrest.